2016
DOI: 10.7883/yoken.jjid2015.111
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Hybrids of <i>Meccus phyllosomus mazzottii</i>, and <i>M. p. pallidipennis</i>, and <i>M. p. phyllosomus</i> to the Transmission of <i>Trypanosoma cruzi</i> in Mexico

Abstract: SUMMARY: The time interval before beginning feeding, feeding time, and defecation delay for 3 Triatominae subspecies, Meccus phyllosomus mazzottii (Ma), M. p. pallidipennis (Pa), and M. p. phyllosomus (Phy) and their laboratory hybrids were evaluated. The mean time interval for beginning feeding was between 0.1 and 10.1 min for all nymphal instars in each cohort, with significant (P < 0.05) differences among hybrids and parental cohorts. Four (both MaPa and MaPhy) hybrid cohorts had similar mean feeding times … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…In addition, Mexican triatomine F1 hybrids also resulted in F1 offspring that were morphologically indistinguishable from one of the parental lines [ 39 ] and in second-generation hybrids (F2) with phenotypic characteristics either specific to those of one of the parents or with intermediate characteristics [ 40 , 41 ]. Considering that some factors can result in an increased risk of T. cruzi transmission to humans and animals (such as vigor [ 42 ] and hybrid fitness [ 43 ]) and that recently it has been reported that hybrids of the T. phyllosoma subcomplex show greater potential to acquire and transmit T. cruzi than parental species [ 44 , 45 ], the study of segregation of external morphology can also be of epidemiological importance [ 37 , 38 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Mexican triatomine F1 hybrids also resulted in F1 offspring that were morphologically indistinguishable from one of the parental lines [ 39 ] and in second-generation hybrids (F2) with phenotypic characteristics either specific to those of one of the parents or with intermediate characteristics [ 40 , 41 ]. Considering that some factors can result in an increased risk of T. cruzi transmission to humans and animals (such as vigor [ 42 ] and hybrid fitness [ 43 ]) and that recently it has been reported that hybrids of the T. phyllosoma subcomplex show greater potential to acquire and transmit T. cruzi than parental species [ 44 , 45 ], the study of segregation of external morphology can also be of epidemiological importance [ 37 , 38 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…These three subspecies have been inter-crossed with each other under laboratory and wild conditions, and fertile hybrids have been obtained (Martínez-Ibarra et al ., 2008 b , 2009). Some triatomine laboratory hybrids have displayed intermediate characteristics or have shown outstanding biological parameters that may confer higher fitness than their parental species (Almeida et al ., 2012; Chávez-Contreras et al ., 2013, Martínez-Ibarra et al ., 2015 b , c ). Wild hybrids have also been associated with resistance to insecticides or have shown higher entomological indices than ‘pure’ species collected (Martínez-Ibarra et al ., 2008 a ; Mas-Coma & Bargues, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…En dos estudios recientes (10,11) sobre los pará-metros biológicos de los híbridos de grupos filogenéticamente cercanos, se ha demostrado el vigor híbrido de los descendientes, con el consecuente aumento del riesgo de transmisión de T. cruzi a las poblaciones humanas. Por ello, el objetivo de este estudio fue conocer los parámetros biológicos de los parentales de T. recurva, M. p. phyllosomus y de sus descendientes.…”
unclassified